Association between systemic inflammation response index and depression in U.S. adults - Qiongqiong Zhan; Yu Wu; Jiaojiao Sun; Yunan Liang; Xinfeng Jiang; Fei Ye (Medicine, 2026)
Inflammatory dysregulation has been implicated in depression; however, the association between the systemic inflammation response index (SIRI), a composite inflammatory marker derived from peripheral neutrophil, monocyte, and lymphocyte counts, and depression in the general adult population remains unclear. This study aimed to examine the association between SIRI and depression among adults from the National Health and Nutrition Examination Survey 2005 to 2016. This cross-sectional study included 24,188 adults with available data on the Patient Health Questionnaire-9 (PHQ-9), blood cell counts, and relevant covariates. SIRI was calculated as neutrophil count × monocyte count/lymphocyte count. Depression was assessed using the PHQ-9, with a score ≥10 indicating clinically relevant depressive symptoms. Multivariable logistic regression, restricted cubic spline analysis, threshold effect analysis, and receiver operating characteristic curve analysis were performed to evaluate the association, nonlinear relationship, and incremental discriminatory value of SIRI. Among 24,188 participants, 2055 (8.50%) had clinically relevant depressive symptoms. Higher SIRI was associated with increased odds of depression after multivariable adjustment (odds ratio = 1.07, 95% confidence interval: 1.02–1.13, P = .004). Compared with the lowest quartile, participants in the highest SIRI quartile had higher odds of depression (odds ratio = 1.26, 95% confidence interval: 1.10–1.44, P < .001). Restricted cubic spline analysis demonstrated a significant nonlinear association between SIRI and depression ( P for nonlinear = .007). Threshold analysis identified an inflection point at approximately 2.58, below which higher SIRI was associated with increased odds of depression, whereas the association plateaued thereafter. Adding SIRI to the basic model slightly improved discrimination (area under the curve: 0.716 vs 0.725). Higher SIRI levels were associated with higher odds of clinically relevant depressive symptoms among adults from the National Health and Nutrition Examination Survey 2005 to 2016, with a nonlinear dose-response pattern. Given the modest effect size and limited improvement in discrimination, SIRI should be interpreted as an auxiliary peripheral inflammatory marker rather than a standalone screening or diagnostic tool. Further prospective studies are required to clarify causality and clinical relevance.